2007
DOI: 10.1016/j.ijgo.2007.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Declining maternal mortality ratio in Uganda: Priority interventions to achieve the Millennium Development Goal

Abstract: Addressing health system issues, especially human resources, and increasingaccess to EmOC could reduce maternal mortality in Uganda and enable the country to achieve the Millennium Development Goal (MDG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 7 publications
2
36
0
Order By: Relevance
“…Arguably, the most important factor implicated in maternal deaths in conflict and post-conflict settings is poor quality or the complete absence of EmOC services. A study in Uganda (49) has revealed that the availability of basic services such as a midwife in a health facility can reduce case fatality rate by up to 80%. Unfortunately such services are largely absent in a lot of conflict settings.…”
Section: Impact Of Armed Conflict On Maternal and Reproductive Healthmentioning
confidence: 99%
“…Arguably, the most important factor implicated in maternal deaths in conflict and post-conflict settings is poor quality or the complete absence of EmOC services. A study in Uganda (49) has revealed that the availability of basic services such as a midwife in a health facility can reduce case fatality rate by up to 80%. Unfortunately such services are largely absent in a lot of conflict settings.…”
Section: Impact Of Armed Conflict On Maternal and Reproductive Healthmentioning
confidence: 99%
“…In Uganda the perinatal mortality rate of 70 deaths per total 1000 births is unacceptably high. Although majority of the deliveries occur at home, substandard obstetric care in the different hospitals continues to be a cause of maternal and newborn morbidity and mortality 2 . Hospital-based studies in low income countries have shown that up to 3 out of 4 perinatal deaths may be due to suboptimal care 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Recent surveys suggest that essential resources are not in place in rural hospitals in low-income countries. [8][9][10] Uganda, a low-income country, faces considerable challenges in the provision of paediatric surgical care. Of its rapidlygrowing population of 31.7 million, 49% is under 15 years of age and 88% lives in rural areas.…”
Section: Introductionmentioning
confidence: 99%